2001
DOI: 10.1046/j.1464-410x.2001.02233.x
|View full text |Cite
|
Sign up to set email alerts
|

Colour Doppler ultrasonography of female urethral vascularization in normal young volunteers: a preliminary report

Abstract: Objective To assess urethral vascularization in healthy young women, using colour Doppler ultrasonography. Subjects and methods Eleven healthy young women volunteers (mean age 33.6 years, range 24±46) with no pelvic¯oor disorders and no history of incontinence were assessed. The subjects underwent colour Doppler ultrasonography using a 4±7 MHz convex broadband transducer. Translabial sagittal scans of the urethra were taken when the subjects had a full bladder, both during the oestrogenic and progestogenic pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
1
11
0
2
Order By: Relevance
“…Our study was designed to identify a correlation between blood supply and urethral pressure profiles, specifically the MUCP. As found in Siracusano et al's study [23,24] on normal volunteers, our indices were best calculated at the segment closest to the external meatus, where the vascularity was most consistently well seen. Although we were able to reproduce the Doppler waveform RI of the periurethral vasculature, we were not able to correlate RI measurements with either complaints of incontinence or urethral pressure measurements.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our study was designed to identify a correlation between blood supply and urethral pressure profiles, specifically the MUCP. As found in Siracusano et al's study [23,24] on normal volunteers, our indices were best calculated at the segment closest to the external meatus, where the vascularity was most consistently well seen. Although we were able to reproduce the Doppler waveform RI of the periurethral vasculature, we were not able to correlate RI measurements with either complaints of incontinence or urethral pressure measurements.…”
Section: Discussionsupporting
confidence: 61%
“…An additional study done by the same investigator evaluated the resistive index of blood flow surrounding the urethra in healthy young continent patients. This study demonstrated that there is a significantly greater resistive index in the anterior proximal urethra than in the distal and middle urethra [23,24]. Others have hypothesized that normal urethral vascularity contributes up to 30% of the total closure pressure [25].…”
Section: Discussionmentioning
confidence: 63%
“…RI was not correlated with parity (Hall et al 2006). In the study by Siracusano et al (Siracusano et al 2001) colour doppler ultrasound of the female urethra in normal fertile young women identified a significantly greater RI in the proximal urethra compared to the middle and distal urethra. Similar results were obtained in the studies by Yang et al (Yang et al 2006) and Wieczorek et al (Wieczorek et al 2011) However all authors emphasised that the differences in obtained RI values may result from general limitations of doppler flow analysis in the urethra.…”
Section: Discussionmentioning
confidence: 97%
“…The values of vascular parameters in the different parts of the urethra have been measured using various techniques (Scholbach et al 2006; Siracusano et al 2001). In the pioneering study by Wieczorek et al, on quantitative assessment of urethral vascularity in nulliparous women, compared to the other parts of the urethra, the midurethra appeared to have the highest value of V mix and the lowest value of A mix.…”
Section: Discussionmentioning
confidence: 99%
“…7 In the present study, in some patients, the ecographic score did not correlate with the MCUP and this ®nding could be an indication that sometimes the UPP is of limited practical value while color ultrasound imaging of the female urethra allowed visualization and classi®cation, using a subjective US score, of the urethral arterial vascularization of normal volunteers and patients a ected by ISD.…”
Section: Discussionmentioning
confidence: 43%